Didactic Content and Experiential Aging Simulation for Developing Patient-Centered Strategies and Empathy for Older Adults - Johnson, Carole E.; Jilla, Anna Marie; Danhauer, Jeffrey L. (Seminars in Hearing, 2018)
The number of people over 65 years of age is increasing, and many of those individuals will have sensorineural hearing loss in addition to other chronic health conditions. Future hearing health care providers need to be sensitive to the needs of elderly patients. The purpose of this article is to describe an experiential learning curriculum used in the Doctor of Audiology program in the Department of Communication Sciences and Disorders at the University of Oklahoma Health Sciences Center. The curriculum uses simulations of sensory disorders common in the elderly to transform knowledge and active experience into patient-centered, empathetic counseling skills and strategies to use with older adults with hearing loss.
Keywords: Counseling; experiential learning; aging simulation